Demonstrating the role of anchoring functionality in interfacial electron transfer dynamics in newly synthesized BODIPY-TiO2 nanostructure composite - Ghosh, Hirendra N.; Das, Amitava; Aute, Sunil; Maity, Partha (New Journal of Chemistry, 2017)
New Bodipy derivatives (Dye 1 and 2) having catechol or resorcinol functionality for anchoring to the nanostructured (NS) TiO2 surfaces have been synthesized. Extended conjugation at one of the two pyrrole rings at the C3 position has helped us in achieving the desired control in tuning the optical and redox properties of the BODIPY based dye molecules. Relative emission quantum yields (em1 = ~52 ± 2% and em2 = 54 ± 2%) are found to be much higher in polar aprotic solvent (acetonitrile), while this are found to be substantially lower for dye 1 in polar protic solvent. Steady state optical absorption studies reveal the formation of a strong charge transfer complex between dye 1 and NS-TiO2, while this interaction is much weaker for dye 2. Transient absorption studies have been carried out for 1/NS-TiO2 and 2/NS-TiO2 systems following excitation with a laser source of 400 nm for understanding the charge transfer dynamics. Results of the transient absorption spectral studies helped in elucidating role of anchoring functionality in influencing the dynamics of the interfacial electron transfer and the charge recombination process in ultrafast time scale.

Donor strapped perylene bisimide macrocycle and its lemniscate dimer with extended charge separation - Veer, Sairam Dnyaneshwar; Goswami, Tanmay; Ravindranathan, Sapna; Gonnade, Rajesh; Kharbanda, Nitika; Ghosh, Hirendra N.; Babu, Sukumaran Santhosh (Inorganic Chemistry Frontiers, 2023)
Macrocyclic structures are fascinating due to their unique design and capability to place chromophores in specific orientations, resulting in exciting optoelectronic properties. However, the synthetic challenges limit the broad exploration of such systems. Herein, we report a thiophene-diacetylene-based ring strapped perylene bisimide macrocycle and its notably different electron transfer features. Single-crystal analysis of the macrocycle pointed to the nearly orthogonal placement of donor-acceptor units, facilitating better electronic communication between them. Interestingly, introduction of an alkyl substituent on the peripheral thiophene ring opened the possibility of forming a higher oligomer macrocycle consisting of two strapped perylene bisimide units. Diffusion and two-dimensional NMR experiments provided insight into the structure of the figure-eight-shaped lemniscate dimer. Transient absorption measurements showed faster electron transfer and extended stabilization of the charge-separated state. The thiophene-diacetylene-based ring is a better donor unit to facilitate rapid electron transfer and extended charge separation in the macrocycle and its lemniscate dimer. The new macrocycle design enables the formation of higher analogs equally capable of stabilizing the charge-separated state. Donor-acceptor (D-A) macrocycle designs position the respective units to achieve ultrafast electron transfer precisely and an extended charge-separated state. Here, we report a D-A macrocycle and its lemniscate dimer molecule with exciting electron transfer features.